Study the Level of English Language Attainment of Secondary School Students: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The language learning scenario would be sensitive and responsive to the variations in the speech communities of the 9 learners if the learners' English language requirements were translated into the language program's aims or objectives. This would make language learning easier by guaranteeing that learners' interest and motivation are maintained. English is a tool of information and communication in this era of knowledge explosion, and teaching it in a school is a skill-oriented activity. Our school's primary goal in teaching English is to allow students' understanding and expression of the language. Aim may be described as a broad statement of purpose and goal that is marked by high precision and specificity.